Nutrient Composition of Dried Seaweed Gracilaria gracilis - Abdullah Rasyid; Ardi Ardiansyah; Ratih Pangestuti (Marine Science Department Diponegoro University, 2019)
The nutrient composition of dried red seaweed Gracilaria gracilis collected from Barru waters, South Sulawesi including proximate, dietary fiber, minerals, fatty acid and amino acid profile has been investigated. The objective of this study was to evaluate the various nutritional parameters of G. gracilis for utilization in human nutrition. Results show that the content of moisture (19.045), protein (10.86%), ash (6.78%), fat (0.18%), carbohydrate (63.13%) and dietary fiber (27.48%) basis on the dry weight. The content of calcium (429.11 mg.100 g-1), sodium (290.89 mg.100 g-1), phosphor (57.01 mg.100 g-1), iron (15.20 mg.100 g-1) and potassium (1380.42 mg.100 g-1). Leucine was the major essential amino acid found to be 9374.22 mg.kg-1, while glutamic acid was the major non-essential amino acid found to be 10848.98 mg.kg-1. Palmitic acid was the major saturated fatty acid found to be 0.08%, while oleic acid was the major unsaturated fatty acid found to be 0.05%. The nutrient composition of G. gracilis was discussed in this study and suggested that the seaweed species have potentially be used as raw material or ingredient of a healthy food for human.